International consumption comparisons : OECD versus LDC - Selvanathan, E. Antony, 1954- (World Scientific, 2003)
This work presents an analysis of consumption patterns in the OECD (rich) and LDC (poor) countries using recent data (1960-1996) and econometric methodology for a number of broadly aggregated consumer goods. The income eleasticity estimates for the 50 or so counries and 10 commodity groups are tabulated. The reliability of these elasticity estimates, and also the demand theory hypotheses, are investigated using simulation techniques.